Social representations and mises-en scène in Bogotá's peasant markets: the good, the institutionalized and the rebel peasant - Garcia Gonzalez, David Fernando; González Vélez, César Augusto; Montenegro Riveros, Mauricio (Cultura y Representaciones Sociales, 2019)
This article is the result of an investigation developed throughout 2017 by three members of the Advertising, Society and Consumption group of the Central University of Bogotá. The objective of the research was to track and analyze the representations that circulate in the Peasant Markets (hereinafter MC) organized by the Mayor’s Office and other institutions of the Bogota district government since 2004. This interest has to do with our conviction, at the same time epistemological and political, that social representations are, as the sociologist Pierre Bourdieu (1995) would say, structuring and structured constructions. In other words, representations are structures of thought internalized by the subjects and, at the same time, historical constructions of a collective nature that help to co-produce the social world. Starting from this premise, we consider that it is pertinent to deconstruct the representations on the field and the peasants that are (re) produced and negotiated in institutional spaces such as the MC. The main objective of this text is, then, to analyze the aesthetic and discursive elements of the various advertising pieces that circulate about CMs, and to determine the nature of the representations that are put into play there. The first section characterizes the corpus of advertising and institutional pieces with which it was worked (which included images, flyers, photographs, videos and press releases), and describes the interpretation process based on the main categories and variables of analysis. Following are some considerations of a conceptual nature with regard to social representations and what we have called “staging”. Finally, in the third part, various aesthetic and discursive elements of the advertising pieces associated with MCs are characterized, and a critical synthesis of the most recurrent representations on the field and the peasants who circulate there is offered.